Study of Organic Fertilizer Modification on The Growth and Yield of Cauliflower (Brassica oleracea) - Renatha, Lorenza; Herawati, Jajuk; Indarwati, Indarwati (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2025)
This study aimed to evaluate the effect of organic fertilizer modification with the addition of Trichoderma sp. on the growth and yield of cauliflower. A Randomized Blok Design (RAK) with five treatments and four replications. The research was conducted from May to November 2024 on the land of Pondok Pesantren Bakti Bapak Emak, Bareng, Jombang. The results showed that; (a) The use of modified organic fertilizer and Trichoderma had a significant effect on cauliflower plant growth (plant height, number of leaves, and root dry weight). The K3 treatment (Nutrizim Granule Organic Fertilizer + Trichoderma) showed better results for cauliflower growth, with plant height reaching approximately 44,25 cm at 6 weeks after planting and producing an average of 21,15. (b) The treatments tested did not have a significant effect on yield parameters. However, field observations indicate that the modified organic fertilizer with added Trichoderma produced better quality cauliflowers, characterized by denser (more compact) curds, a clean yellowish-white color, and overall improved appearance.